Dialogue as an Educational Principle in the "Philosophy of History" Course to Overcome Conflicts of Historical Memory in the Context of Ukraine’s Humanitarian Security - Aleksandrova , Olena; Omelchenko Yuriі (Skhid, 2024)
The article examines the essence of dialogue and its potential application for mit-igating and/or overcoming conflicts of historical memory. Recognizing education as the foundation for social cohesion in Ukraine, the practical dimension demonstrates how Philosophy of History can be taught through dialogue and applied as a principle of social unity in addressing complex issues of historical memory and overcoming historical traumas. Such dialogue should entail: prior rational processing of historical memory content; mechanisms for overcoming opposing viewpoints; the establish-ment of a communicative space for discussing historical memory; re-evaluation of one’s own "Self" and the critical analysis of personal views and beliefs, as well as one’s historical memory; concessions and self-restraint in the perception of differing positions among communication participants; and the creation of consensus through the re-evaluation of alternative perspectives on historical events. Conflicts of histori-cal memory unfold across various dimensions and can be classified as: interstate; intrastate; between different social groups; and between specific social groups and the academic community. In the context of ensuring humanitarian security in Ukraine and addressing conflicts of historical memory, it is important to consider that after the war, three primary variants of social dialogue are likely to be observed within Ukrainian society: consensus as voluntary favorable attitude towards realities; inclu-sion as the opportunity for free expression of opinions; and participation as the realization of one’s own ideas by interested social actors. The dominant variant form of dialogue regarding historical memory will depend on the monopoly of the current power structure, the strength of civil society, and the specifics of the social dialogue between them.